2012
DOI: 10.5333/kgfs.2012.32.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Fractionation and Buffer Solubility of Forage Sources on In Vitro Fermentation Characteristics, Degradability and Gas Production

Abstract: Buffer solubility and protein fractionation were evaluated from the hays (timothy, alfalfa and klein) and straws (tall fescue and rice), and in vitro trial was conducted to examine the effect of buffer extraction on fermentation characteristics, degradability and gas (CO2 and CH4) production. Buffer soluble protein (SP) content and A fraction in total protein were highest in alfalfa hay as 61% and 41.77%, respectively while lowest in rice straw (42.8% and 19.78%, respectively). No difference was observed in B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
5
0
3
Order By: Relevance
“…The strong relationship between total gas production and EDDM has been previously reported (Jin et al, 2012). Regardless of defaunation, more gas was produced from forages than from cellulose (Table 4).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The strong relationship between total gas production and EDDM has been previously reported (Jin et al, 2012). Regardless of defaunation, more gas was produced from forages than from cellulose (Table 4).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, ryegrass showed similar results in comparison with cellulose, and seemed to be more potent in increasing total VFA concentration than both rice straw and tall fescue. This might be associated with the relatively low degree of lignification and high buffer solubility in ryegrass (Jin et al, 2012). It can be indicated that degradation of ryegrass is less limited by lignin and more rapidly available for rumen microbes, contribution to more VFA production.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1). 이것은 기존 연구에서 보고된 각 단백질의 N 분획과 전체적으로 유사하였으나 (Licitra et al, 1996;Jin, 2011;Choi, 2015), 채종박의 경우 B 2 fraction이 A와 B 1 fraction보다 다소 높게 나타났다. .…”
Section: Cncps Fraction별 대표사료 선정unclassified
“…단백질 fraction별 대표사료를 선정하기 위해 기존의 문 헌을 통해 후보사료를 1차 검색 후 그 중 fraction별 함유량 이 높고 국내에 사용되고 있는 사료로 선발하였다 (Choi, 2003;Choi et al, 2015;Jin, 2011;Licitra et al, 1996).…”
Section: Cncps Fraction별 대표사료 선정unclassified
“…(Table 1). 이것은 기존 연구에 서 보고된 각 단백질의 N 분획과 전체적으로 유사하였다 (Choi, 2003;Jin, 2011;Licitra et al, 1996) Treatments were TMR only (control), TMR with rapeseed meal (AB1), TMR with soybean meal (B2) and TMR with perilla meal (B3C), respectively. b) Standard error of the mean.…”
Section: Cncps Fraction별 대표사료 선정mentioning
confidence: 99%